PENGARUH PROJECT-BASED LEARNING DIGITAL TERHADAP KETERAMPILAN MENULIS TEKS ANEKDOT: MEDIASI LITERASI DAN BERPIKIR KRITIS - Zherry Putria Yanti; Ermanto Ermanto; Havid Ardi; Atika Gusriani; Ranti Karmila (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aims to examine the effect of digital Project-Based Learning on students’ skills in writing anecdotal texts and to analyze the mediating role of digital literacy and critical thinking among high school students. The study employed a quasi-experimental design using a pretest–posttest control group model. Data were collected through writing tests, a digital literacy questionnaire, and a critical thinking instrument. Data analysis was conducted using comparative tests to compare learning outcomes between the experimental and control groups, as well as hierarchical multiple regression analysis to test the mediation model. The results of the study indicate that Digital PjBL is effective in improving anecdotal text-writing skills compared with conventional learning. Digital literacy and critical thinking act as partial mediators explaining how this learning model influences the quality of students’ writing. Theoretically, this study contributes by offering a mediation model that integrates digital learning environments with higher-order thinking processes in writing instruction. In practice, the findings of this study imply the need for the explicit integration of digital literacy and critical thinking into project-based learning designs to make writing instruction more effective and meaningful.